2016
DOI: 10.1136/annrheumdis-2015-208873
|View full text |Cite
|
Sign up to set email alerts
|

Patients with seronegative RA have more inflammatory activity compared with patients with seropositive RA in an inception cohort of DMARD-naïve patients classified according to the 2010 ACR/EULAR criteria

Abstract: ObjectivesTo compare the presentation of seropositive and seronegative early rheumatoid arthritis (RA) in disease-modifying antirheumatic drug (DMARD)-naïve patients classified according to the 2010 American College of Rheumatology (ACR)/European League Against Rheumatism (EULAR) criteria.MethodsAll patients had symptom duration from first swollen joint <2 years and were DMARD naïve with an indication for DMARD treatment. Patients were stratified as seropositive (positive rheumatoid factor (RF)+ and/or anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
91
1
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(110 citation statements)
references
References 20 publications
8
91
1
10
Order By: Relevance
“…The association between the presence of additional autoantibodies and longer symptom duration is in line with a previous publication 13. It was recently reported that seronegative individuals have higher joint counts at presentation 5. We found in addition that increasing numbers of autoantibodies are associated with lower tender joint counts (and swollen joint counts in EAC).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The association between the presence of additional autoantibodies and longer symptom duration is in line with a previous publication 13. It was recently reported that seronegative individuals have higher joint counts at presentation 5. We found in addition that increasing numbers of autoantibodies are associated with lower tender joint counts (and swollen joint counts in EAC).…”
Section: Discussionsupporting
confidence: 92%
“…Seropositive patients also have a worse disease outcome with more radiological damage over time 4. In contrast, seronegative patients have recently been described to have more joint inflammation at initial presentation 5. Even though novel autoantibodies may be discovered in the future, seropositive and seronegative RA as defined at the moment is likely to differ in underlying pathophysiology and phenotype 5 6…”
Section: Introductionmentioning
confidence: 99%
“…Although it is not directly evaluated in the study of Nordberg et al ,5 the results of this study suggest that the increase in sensitivity is largely confined to patients who are ACPA positive because patients who are ACPA negative now require more inflamed/involved joints to be classified as RA than those who are ACPA positive. Further studies are needed to verify this.…”
Section: Changes In Test Characteristicsmentioning
confidence: 61%
“…The study of Nordberg et al 5 makes us think about the consequences of the novel criteria for the phenotype of RA. According to the 1987 criteria, the characteristic phenotype of RA consists of symmetric polyarthritis of small joints with morning stiffness (ignoring the features of long-standing disease nodules and erosions).…”
Section: Changes In Classification Criteriamentioning
confidence: 99%
“…More recently, antibodies against other posttranslationally modified proteins, i.e., carbamylated [2] and acetylated proteins were identified [3]. Seropositive RA is associated with increased radiographic progression and joint damage [27], while seronegative RA patients have higher inflammation parameters at presentation [28]. Furthermore, not only positivity for a single autoantibody but rather the conjoined presence of multiple autoantibodies might be relevant for characterizing distinct phenotypes of RA patients [29].…”
Section: Autoantibodies In Ramentioning
confidence: 99%